2012
DOI: 10.1007/s11033-012-1933-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of Metadherin–SND1 interaction in colon cancer

Abstract: The interaction between Metadherin (MTDH) and Staphylococcal nuclease homology domain containing 1 (SND1) is involved in tumorigenesis and tumor progression of several human malignancies. However, its roles in colon cancer are still unclear. To investigate the clinical value of MTDH and SND1 expression in colon cancer. Immunohistochemical staining was performed to detect the expression of MTDH and SND1 using human colon cancer and their corresponding non-cancerous colon tissues from 196 patients' biopsies. Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…In human colon cancer, SND1 is upregulated and contributes to cancer development at the early stages via activation of the Wnt signaling pathway (33). Meanwhile, SND1 could also interact with AEG-1 in colon cancer (29). In the present study, we demonstrate that SND1 plays important roles in breast cancer metastasis.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In human colon cancer, SND1 is upregulated and contributes to cancer development at the early stages via activation of the Wnt signaling pathway (33). Meanwhile, SND1 could also interact with AEG-1 in colon cancer (29). In the present study, we demonstrate that SND1 plays important roles in breast cancer metastasis.…”
Section: Discussionsupporting
confidence: 56%
“…SND1 upregulation has been reported in various malignant tumors, such as hepatocellular carcinoma (27), prostate cancer (28), and colon cancer (29). The molecular mechanisms for the involvement of SND1 in tumorigenesis of different types of cancers appear to be diverse.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies analysing the AEG-1 expression in CRC showed no or only slight nuclear expression (214,247,310,311). The differences in AEG-1 localisation between our study and the other studies performed in CRC, might be due to different antibodies and staining The AEG-1 expression did not differ between the distant normal mucosa and the adjacent mucosa, neither in the cytoplasm nor in the nucleus, and was therefore considered as one group for further analyses to increase the sample size.…”
Section: Resultsmentioning
confidence: 92%
“…The determination of these elements and the impact of mutations is very challenging. We also analysed the corresponding normal mucosa, whenever available, to be able to identify (214,247,310,311).…”
Section: Resultsmentioning
confidence: 99%
“…85 Immunohistochemical staining of samples from human colon cancer and their corresponding non-cancerous colon tissues revealed simultaneous increase of expression of AEG-1 and TSN in tumor samples compared with paired non-cancerous colon tissues. 77 Importantly, their positive expression was both significantly associated with nodal status, pathological stage and differentiation. Moreover, the overall survival rate in colon cancer patients with positive expression of both AEG-1 and TSN was significantly reduced proposing the co-expression of AEG-1 and TSN as a potent marker for prediction of the prognosis in colon cancer.…”
Section: Role Of Tsn In Carcinogenesis and Cell Deathmentioning
confidence: 98%